(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: This study aims to determine the improvement of student learning outcomes and activities on the subject matter of functions by applying the discovery learning model in class VIII-1 of SMP Negeri 1 Tigapanah in the 2018/2019 school year. This classroom action research took place in two cycles. The study was carried out from August 2018 to November 2018. The research subjects were all students of class VIII-1 SMP Negeri 1 Tigapanah for the academic year 2018/2019, totaling 32 students. Data on learning outcomes were obtained through formative tests, while data on student learning activities were obtained through observation. The results showed that student learning outcomes increased by applying the discovery learning model in Formative I and Formative II increased from an average value of 72 to 80 and classical completeness from 66% to 88% in Cycle II. So that there is an increase of 22%, the data shows an increase and is complete in accordance with the KKM. The results showed that students’ learning activities increased by applying the discovery learning model as indicated by the percentage of active students in Cycle I of 72% and in Cycle II of 91% with an increase of 19%. Keywords: Discovery, Complete Learning Outcomes Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan ketuntasan hasil dan aktifitas belajar siswa pada materi pokok fungsi dengan menerapkan model pembelajaran discovery di kelas VIII-1 SMP Negeri 1 Tigapanah tahun pelajaran 2018/2019. Penelitian tindakan kelas ini berlangsung dalam dua siklus. Penelitian dilaksanakan pada bulan Agustus 2018 sampai dengan bulan November 2018. Subjek penelitian adalah seluruh siswa kelas VIII-1 SMP Negeri 1 Tigapanah tahun pelajaran 2018/2019 yang berjumlah 32 siswa. Data hasil belajar diperoleh melalui tes formatif, sedangkan data aktifitas belajar siswa diperoleh melalui observasi. Hasil penelitian menunjukkan bahwa hasil belajar siswa meningkat dengan menerapkan model pembelajaran discovery pada Formatif I dan Formatif II meningkat dari nilai rata-rata 72 menjadi 80 dan ketuntasan klasikal dari 66% menjadi 88% pada Siklus II. Sehingga terjadi peningkatan sebesar 22%, data tersebut menunjukkan peningkatan dan tuntas sesuai dengan KKM. Hasil penelitian menunjukkan bahwa aktifitas belajar siswa meningkat dengan menerapkan model pembelajaran discovery ditunjukkan dengan persentase siswa aktif Siklus I sebesar 72% dan pada Siklus II sebesar 91% dengan peningkatan 19%. Kata Kunci: Discovery, Ketuntasan Hasil Belajar